Analisis Saluran Pemasaran Manggis Garcinia Mangosta L. Di Kabupaten Bogor, Jawa Barat - Doni Sahat Tua Manalu; Vela Rostwentivaivi; Isma Nurjanah; Diana Indah Ramadhani; Anie Puspita Sari; Diva Nurfitrianti Azizah; Yunus Al Gaza (Pusat Riset dan Inovasi Nasional, 2024)
Indonesia is one of the countries that has very abundant horticultural resources and has the potential for national competitiveness globally. One of the horticultural commodities that has become a superior product in Indonesia is Mangosteen (Garcinia mangostana L.) dubbed as the Queen of Fruits. This study aims to determine the marketing channels of mangosteen commodities, analysis of marketing margin costs, profits, and Farmer's Share in Karacak Village, Leuwiliang District, Bogor Regency, West Java. The determination of the research area is determined intentionally (Purposive Method). The method used for sampling using the Snowball Sampling method is selected based on previous sample information.